Two-dimensional bimetallic organic nanosheet loaded silicon-carbon composite material as well as preparation method and application thereof

By introducing polydopamine-coated silicon powder in the Ni-Co-BDC synthesis process, a two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite Si@C/Ni-Co-BDC was prepared, which solved the problems of energy density and volume changes of lithium-ion batteries, and achieved the improvement of high specific capacity and electrochemical performance.

CN119581515APending Publication Date: 2025-03-07CHAOHU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411658243.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The energy density of existing lithium-ion batteries is limited, and silicon, as a high specific capacity material, changes dramatically during charging and discharging, resulting in attenuation of battery capacity, limiting its application.

Method used

Polydopamine-coated silicon powder was introduced during Ni-Co-BDC synthesis by in-situ self-assembly method to prepare two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite Si@C/Ni-Co-BDC.

Benefits of technology

This material significantly improves electrochemical performance and specific capacity by increasing redox active sites and improving structural stability, and extends the cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581515A_ABST
    Figure CN119581515A_ABST
Patent Text Reader

Abstract

The invention relates to a two-dimensional bimetal organic nanosheet loaded silicon-carbon composite material and a preparation method and application thereof, and belongs to the technical field of preparation of lithium ion power battery electrode materials.Firstly, dopamine is polymerized on the surface of silicon powder in situ, and the silicon-carbon composite material (Si-C) is obtained after high-temperature calcination; then, terephthalic acid, cobalt chloride hexahydrate, nickel chloride hexahydrate and Si-C are added into a mixed solution prepared from N, N-dimethylformamide, deionized water and ethyl alcohol; and after dissolving, injecting triethylamine and stirring, sealing the container after light gray precipitates appear, continuously performing ultrasonic treatment, performing centrifugal washing for multiple times, and drying at room temperature to obtain the product Si (at) C / Ni-Co-BDC composite material. Compared with pure silicon powder and silicon-carbon composite materials, the composite material Si (at) C / Ni-Co-BDC has better structural stability and rich redox active sites, the lithium storage performance of the material can be further optimized, and the composite material has better application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of lithium ion power battery electrode materials, and specifically relates to a two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in a variety of energy storage devices, such as electric vehicles, portable electronic devices, and various energy storage systems. However, the energy density of existing lithium-ion batteries is severely limited due to the inherent chemical properties of electrode materials. For example, graphite, a commonly used commercial negative electrode material, has a specific capacity of only 372 mAh g -1 , which cannot meet the growing demand for energy density. In order to overcome this defect, new electrode materials must be developed for high-capacity lithium-ion batteries.

[0003] Silicon (Si) has the highest known theoretical specific capacity (4200mAh g -1 ) of lithium-ion battery negative electrode materials, coupled with its relatively moderate lithium insertion potential (~0.4V vs.Li + / Li), abundant reserves and environmental friendliness, are expected to replace graphite as the negative electrode material for the next generation of high energy density lithium batteries. However, during the charge and discharge process, the generation and decomposition of silicon-lithium alloys are accompanied by huge volume changes, with the maximum expansion reaching 320%. Such a drastic volume change will cause the battery capacity to decay rapidly, severely limiting the further application of silicon negative electrodes in lithium-ion batteries.

[0004] At present, the mainstream method to solve the above problems is to combine silicon with carbon materials, and use the spatial confinement of carbon materials to buffer the volume changes during charging and discharging. However, due to the low intrinsic theoretical capacity of carbon materials, combining silicon with carbon greatly reduces the specific capacity that can be achieved by the composite system and the improvement of cycle stability is also relatively limited. Summary of the invention

[0005] The purpose of the present invention is to provide a two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material and a preparation method and application thereof in order to solve the above-mentioned problems.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] As a first aspect of the present invention, a two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material is provided. The two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material is obtained by introducing a polydopamine-coated silicon powder-derived silicon-carbon composite material Si@C into the synthesis process of Ni-Co-BDC by an in-situ self-assembly method.

[0008] As a second aspect of the present invention, there is also provided an application of the above-mentioned two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material in the field of lithium battery electrodes.

[0009] As a third aspect of the present invention, a lithium battery electrode material is also provided, which is prepared by the following steps:

[0010] (A) mixing the above-mentioned two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 to obtain a mixture, adding N-methylpyrrolidone to the mixture, and ultrasonically dispersing the mixture to obtain a colloidal black liquid, and dispersing the slurry using a high-speed internal rotation homogenizer, repeating 5 to 7 times per minute to obtain a uniform Si@C / Ni-Co-BDC black colloidal slurry;

[0011] (B) The Si@C / Ni-Co-BDC black colloidal slurry is uniformly coated on the copper foil current collector and placed in a vacuum oven for drying. The temperature is set at 60-80°C and the drying time is 12-24 hours to obtain the Si@C / Ni-Co-BDC lithium battery electrode material.

[0012] As a fourth aspect of the present invention, there is also provided a method for preparing the two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material as described above, comprising the following steps:

[0013] (1) stirring and dispersing silicon powder in deionized water, adding dopamine hydrochloride and a buffer reagent tris(hydroxymethylaminomethane) to obtain a mixed solution, stirring the mixed solution at room temperature, centrifuging and washing with deionized water to obtain polydopamine-coated silicon powder Si@PDA, drying and calcining under nitrogen protection to obtain a silicon-carbon composite material Si@C;

[0014] (2) adding terephthalic acid, cobalt chloride hexahydrate, nickel chloride hexahydrate and the silicon-carbon composite material into a mixed solution containing N,N-dimethylformamide, deionized water and ethanol to dissolve for later use;

[0015] (3) First, triethylamine is injected into the mixed solution obtained in step (2) and stirred until a light gray precipitate appears, and then the container is sealed and ultrasonic treatment is continued. Then, the reaction system is centrifuged and washed with ethanol, and dried at room temperature to obtain the two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material Si@C / Ni-Co-BDC.

[0016] A further improvement is that in step (1), the method for preparing the silicon-carbon composite material Si@C comprises the following steps:

[0017] (1-1) 0.1-0.3 g of silicon powder is dispersed in 40-60 ml of deionized water, and then 0.2-0.5 g of dopamine hydrochloride and 1-3 g of tris(hydroxymethyl)aminomethane are added under stirring, and the mixture is stirred at room temperature for 10-15 h. The mixture is washed with deionized water and centrifuged and dried to obtain polydopamine-coated silicon powder Si@PDA;

[0018] (1-2) The Si@PDA obtained in step (1-1) is placed in a tubular furnace, kept at 500-700° C. for 1-3 h under nitrogen protection, and naturally cooled to obtain a silicon-carbon composite material Si@C.

[0019] A further improvement is that in step (2), the volume ratio of N,N-dimethylformamide, deionized water and ethanol in the mixed solution is (12-16):1:1.

[0020] A further improvement is that in step (3), the amount of triethylamine added is 0.4 to 1 mL, the stirring time is 10 to 20 min, the continuous ultrasonic treatment time is 6 to 8 h, and the ultrasonic frequency is 40 kHz.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention adopts an in-situ self-assembly strategy, introduces a silicon-carbon composite material derived from polydopamine-coated silicon powder during the synthesis of Ni-Co-BDC, and prepares a two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material. This not only utilizes the characteristic of Ni-Co-BDC itself having abundant lithium storage active sites to increase the redox active sites, thereby improving the specific capacity of the composite system, but also can further improve the structural stability of the material through the loading of Ni-Co-BDC on the silicon-carbon composite material, thereby significantly improving the electrochemical performance.

[0023] (2) The two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material Si@C / Ni-Co-BDC provided by the present invention has better structural stability and abundant redox active sites compared with pure silicon powder and pure silicon-carbon composite materials, and fully utilizes the dual effects of carbon coating and two-dimensional bimetallic organic nanosheet loading to further improve the lithium storage performance of the material. At the same time, the preparation process of the material has low equipment requirements, the raw material price is cheap, and it has good prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction spectra (XRD) of Si, Si@PDA, Si@C and Si@C / Ni-Co-BDC provided by the present invention;

[0025] Figure 2Scanning electron microscope photos (SEM) of Si (a), Si@PDA (b), Si@C (c) and Si@C / Ni-Co-BDC (d) provided by the present invention;

[0026] Figure 3 Elemental mapping of Si@C / Ni-Co-BDC provided by the present invention;

[0027] Figure 4 This is the electrochemical cycle performance diagram of Si, Si@PDA, Si@C and Si@C / Ni-Co-BDC provided by the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above application content.

[0029] 1. Materials and Methods

[0030] The methods used in this example are conventional methods known to those skilled in the art unless otherwise specified, and the reagents and other materials used are commercially available products unless otherwise specified. 2. Specific embodiments

[0032] Example 1 Composite material Si@C / Ni-Co-BDC

[0033] 1.1 Preparation of silicon-carbon composite materials

[0034] 0.1-0.3 g of silicon powder was dispersed in 40-60 ml of deionized water, and then 0.2-0.5 g of dopamine hydrochloride and 1-3 g of tris(hydroxymethyl)aminomethane were added under stirring, and the mixture was stirred at room temperature for 10-15 h. After washing with deionized water and centrifugally dried, polydopamine-coated silicon powder Si@PDA was obtained;

[0035] The polydopamine-wrapped silicon is placed in a tubular furnace, kept at 500-700° C. for 1-3 hours under nitrogen protection, and naturally cooled to obtain a silicon-carbon composite material Si@C.

[0036] 1.2 Preparation of Si@C / Ni-Co-BDC composite materials

[0037] Terephthalic acid, cobalt chloride hexahydrate, nickel chloride hexahydrate and the silicon-carbon composite material obtained above in a mass ratio of 2:2:1:3 are added to a mixed solution prepared by N,N-dimethylformamide, deionized water and ethanol in a volume ratio of (12-16):1:1.

[0038] After the metal salt and organic ligand are dissolved, 0.4-1 mL of triethylamine is injected and stirred for 10-20 min, and a light gray precipitate appears. Then the container is sealed and ultrasonic treatment is continued for 6-8 h at an ultrasonic frequency of 40 kHz. The reaction system is centrifuged and washed with ethanol several times, and the product Si@C / Ni-Co-BDC is obtained after drying at room temperature.

[0039] X-ray diffraction analysis and scanning electron microscopy analysis were carried out on Si, Si@PDA, Si@C and prepared Si@C / Ni-Co-BDC.

[0040] like Figure 1 As shown, the XRD pattern shows that compared with Si, Si@PDA, and Si@C, Si@C / Ni-Co-BDC has a diffraction peak belonging to Ni-Co-BDC in addition to the diffraction peak of silicon.

[0041] Figure 2 These are the SEM images of Si, Si@PDA, Si@C and Si@C / Ni-Co-BDC. It can be seen that the pure silicon powder presents a spherical morphology, the surface of Si@PDA is coated with a layer of film-like polymer, the carbon layer on the surface of Si@C is relatively rough, and Si@C / Ni-Co-BDC presents the morphology of a silicon-carbon composite material loaded by two-dimensional bimetallic organic nanosheets Ni-Co-BDC.

[0042] Figure 3 This is the element distribution map of Si@C / Ni-Co-BDC. The five elements C, O, Ni, Co and Si are evenly distributed in this material.

[0043] Example 2 Preparation of Si@C / Ni-Co-BDC lithium battery electrode material

[0044] 2.1 Preparation process

[0045] The Si, Si@C and Si@C / Ni-Co-BDC materials prepared in Example 1 were selected and mixed with acetylene black and polyvinylidene fluoride (PVDF) (binder) at a mass ratio of 8:1:1, and then N-methylpyrrolidone was added to the mixture, and ultrasonic dispersion was performed to obtain a colloidal black liquid; the slurry was dispersed with a high-speed internal rotation homogenizer, and the process was repeated 5 to 7 times per minute to obtain uniform Si, Si@C and Si@C / Ni-Co-BDC black colloidal slurries;

[0046] The above black colloidal slurry was evenly coated on the pre-treated copper foil current collector, with a loading of 1-2 mg cm -2The electrode thickness is ~20μm, and it is placed in a vacuum oven for drying. The temperature is set at 60-80℃ and the drying time is 12-24h. Finally, Si, Si@C and Si@C / Ni-Co-BDC lithium battery electrode materials are obtained.

[0047] 2.2. Battery assembly and testing

[0048] The prepared electrodes were placed in a homemade stainless steel battery mold for testing. High-purity lithium sheets were used as negative electrodes, polypropylene porous membranes (Celgard 2400) were used as separators, and the electrolyte was a mixture of 1 mol / L LiPF6 dissolved in ethylene carbonate and diethyl carbonate (mass ratio 1:1). The battery was assembled in a glove box filled with high-purity argon. On the LAND-CT2001C system, the voltage range was fixed (5mV-3.0V vs.Li + / Li) to test the battery charge and discharge. The test current density is 0.1C, where 1C is equal to 1000mA g -1 .

[0049] Figure 4 For Si, Si@C and Si@C / Ni-Co-BDC lithium battery electrode materials at 100mA g -1 Electrochemical cycling performance diagram of Si and Si@C shows 197 mAh g after 50 cycles. -1 and 596mAh g -1 The reversible capacity of Si@C / Ni-Co-BDC is lower than that of Si@C / Ni-Co-BDC, while Si@C / Ni-Co-BDC still maintains 1137 mAh g after 50 cycles. -1 The raw materials for the preparation of this material are cheap, the equipment requirements are low, and it has good prospects.

[0050] The above description shows and describes several preferred embodiments of the invention, but as mentioned above, it should be understood that the invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and modifications made by those skilled in the art should be within the scope of protection of the claims attached to the invention without departing from the spirit and scope of the invention.

Claims

1. A two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material, characterized in that: The two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material is obtained by introducing polydopamine-coated silicon powder and deriving the silicon-carbon composite material Si@C during the synthesis of Ni-Co-BDC by an in-situ self-assembly method.

2. An application of the two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material as claimed in claim 1 in the field of lithium battery electrode materials.

3. A lithium battery electrode material, characterized in that: Prepared by the following steps: (A) mixing the two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material as claimed in claim 1 with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 to obtain a mixture, adding N-methylpyrrolidone to the mixture, and ultrasonically dispersing the mixture to obtain a colloidal black liquid, and dispersing the slurry using a high-speed internal rotation homogenizer, repeating 5 to 7 times per minute to obtain a uniform Si@C / Ni-Co-BDC black colloidal slurry; (B) The Si@C / Ni-Co-BDC black colloidal slurry is uniformly coated on the copper foil current collector and placed in a vacuum oven for drying. The temperature is set at 60-80°C and the drying time is 12-24 hours to obtain the Si@C / Ni-Co-BDC lithium battery electrode material.

4. A method for preparing the two-dimensional bimetallic organic nanosheet-supported silicon-carbon composite material as claimed in claim 1, characterized in that: The following steps are involved: (1) stirring and dispersing silicon powder in deionized water, adding dopamine hydrochloride and a buffer reagent tris(hydroxymethylaminomethane) to obtain a mixed solution, stirring the mixed solution at room temperature, centrifuging and washing with deionized water to obtain polydopamine-coated silicon powder Si@PDA, drying and calcining under nitrogen protection to obtain a silicon-carbon composite material Si@C; (2) adding terephthalic acid, cobalt chloride hexahydrate, nickel chloride hexahydrate and the silicon-carbon composite material into a mixed solution containing N,N-dimethylformamide, deionized water and ethanol to dissolve for later use; (3) First, triethylamine is injected into the mixed solution obtained in step (2) and stirred until a light gray precipitate appears, and then the container is sealed and ultrasonic treatment is continued. Then, the reaction system is centrifuged and washed with ethanol, and dried at room temperature to obtain the two-dimensional bimetallic organic nanosheet-loaded silicon-carbon composite material Si@C / Ni-Co-BDC.

5. The method for preparing a two-dimensional bimetallic organic nanosheet-supported silicon-carbon composite material according to claim 4, characterized in that: In step (1), the method for preparing the silicon-carbon composite material Si@C comprises the following steps: (1-1) 0.1-0.3 g of silicon powder is dispersed in 40-60 ml of deionized water, and then 0.2-0.5 g of dopamine hydrochloride and 1-3 g of tris(hydroxymethyl)aminomethane are added under stirring, and the mixture is stirred at room temperature for 10-15 h. The mixture is washed with deionized water and centrifuged and dried to obtain polydopamine-coated silicon powder Si@PDA; (1-2) The Si@PDA obtained in step (1-1) is placed in a tubular furnace, kept at 500-700° C. for 1-3 h under nitrogen protection, and naturally cooled to obtain a silicon-carbon composite material Si@C.

6. The method for preparing a two-dimensional bimetallic organic nanosheet-supported silicon-carbon composite material according to claim 4, characterized in that: In step (2), the volume ratio of N,N-dimethylformamide, deionized water and ethanol in the mixed solution is (12-16):1:

1.

7. The method for preparing a two-dimensional bimetallic organic nanosheet-supported silicon-carbon composite material according to claim 4, characterized in that: In step (2), the mass ratio of terephthalic acid, cobalt chloride hexahydrate, nickel chloride hexahydrate and silicon-carbon composite material is 2:2:1:

3.

8. The method for preparing a two-dimensional bimetallic organic nanosheet-supported silicon-carbon composite material according to claim 4, characterized in that: In step (3), the amount of triethylamine added is 0.4-1 mL, the stirring time is 10-20 min, the continuous ultrasonic treatment time is 6-8 h, and the ultrasonic frequency is 40 kHz.

Citation Information

Cited By

  • Aero-engine blade and preparation method thereof

    CN120081673A